American and Indonesian Values of Woman Identity and Their influence on Womanâs Pursuit of Happiness as reflected in Elizabeth Gilbertâs Eat Pray Love (2006) and Nh. Diniâs Pada Sebuah Kapal (1973): A Comparative Study - , Edi Ardian, Prof. Dr. C Soebakdi Soemanto, SU. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The differences in cultural backgrounds influence the content of literary works, despite the same theme addressed. The purpose of the research is to compare and contrast an American novel Eat Pray Love (EPL) and Indonesian PadaSebuahKapal(PSK) for differences and similarities in the sense of how different cultures influencethe heroine in each novel in her pursuit of happiness. For that purpose, a thematic, descriptive, and comparative analysis is conducted to answer two research problems: 1) what constraint each heroine has to face in her attempts to achieve happiness